2016
DOI: 10.1080/1475939x.2016.1174730
|View full text |Cite
|
Sign up to set email alerts
|

TPACK in teacher education: are we preparing teachers to use technology for early literacy?

Abstract: This study examines if and how five teacher education institutes are helping students to develop the technological pedagogical content knowledge needed to effectively use technology for early literacy. Focus group discussions were held with teacher educators in which their responses to expert recommendations were probed. Findings indicate that, currently, very little attention is specifically given to the knowledge that teachers need to foster early literacy through the use of technology. This is due to multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(137 citation statements)
references
References 40 publications
(48 reference statements)
4
95
0
10
Order By: Relevance
“…The complexity of their integration comes from an appreciation of the rich connections among these constructs and the ways in which these can be developed in a dynamic telecollaborative context. In using telecollaboration and the CLIL approach within a TPACK framework, this study has pursued to provide such view so as to improve pre-service teacher competences and knowledge in tertiary education, and to try to facilitate teacher educators' experimentation with (domain-specific) technologies (Voogt & McKenney, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of their integration comes from an appreciation of the rich connections among these constructs and the ways in which these can be developed in a dynamic telecollaborative context. In using telecollaboration and the CLIL approach within a TPACK framework, this study has pursued to provide such view so as to improve pre-service teacher competences and knowledge in tertiary education, and to try to facilitate teacher educators' experimentation with (domain-specific) technologies (Voogt & McKenney, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the framework has been successfully applied and validated to assess and bolster teachers' capacity for ICT integration (Archambault & Crippen, 2009;Niess et al, 2010-11), to measure teachers' understanding of technology (Archambault, 2016;Phillips, 2016) and to evaluate teacher training experiences (Abbitt, 2011) and students' TPACK competence through digital portfolio ratings (Koehler, Greenhalgh, Rosenberg & Keenan, 2017) Teachers' use of ICT has been shown to improve after TPACK development efforts (Mishra & Koehler, 2006) and research has demonstrated that teachers with appropriate TPACK skills tend to use technology to enrich or supplement the existing curriculum and to provide an enriched pedagogical approach (Ertmer, Ottenbreit-Leftwich, Sadik, Sendurer, & Sendurer, 2012). However, research has also pointed out that there are very few courses or learning opportunities through which pre-service teachers can develop integrated knowledge (Voogt & McKenney, 2016) and, thus, in-service teachers are still concerned regarding the suitability of ICT to enhance collaborative learning practices. Maximizing teacher training has been considered promising to eradicate those concerns (García-Valcárcel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, developing TPACK is fundamental for teachers and educators to implement technology in courses not merely focused on technology skills. Voogt and McKenney (2017), stated that 'it enables teachers to select and use hardware and software, identify the affordances (or lack thereof) of specific features and use the tools in pedagogically appropriate and effective ways. In this study, the seven-factor model based on Mishra and Koehler (2006) was used to analyse 574 teacher educators across six countries.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, there is a need for a conceptual framework for the effective use of technological developments by teachers within educational activities. According to the technological pedagogical content knowledge (TPCK) model, it is expected that educational technologies will be used properly within the framework of teaching and learning activities (Harris, Mishra & Koehler, 2009;Kabakci-Yurdakul, 2011;Shin et al, 2009;Voogt & McKenney, 2017). The developed TPCK model emphasizes the importance and necessity of uniting technological, pedagogical and content knowledge of a teacher with an appropriate approach to effectively complete technology-supported teaching.…”
Section: Introductionmentioning
confidence: 99%